2020
DOI: 10.3776/tpre.2020.v10n2p119-139
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Rural Gifted Education in Texas

Abstract: Rural gifted education historically has struggled with its own identity. Limited research exists on rural gifted programming, effective ways to implement gifted pedagogy and curriculum, and how to maximize limited time, resources, and funding. Rural communities are complex, dynamic entities, full of nuances and guided by a sense of place and rural culture. Faced with limited funding, resources, and time, rural gifted programs struggle to provide consistent quality enrichment to gifted learners. This study refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…While they agreed that mandates were important, gifted education was equally so. Lewis and Boswell (2020) also found that consistent time blocks were an important aspect for gifted programs, from the perspective of teachers.…”
Section: How Does (Or Should) Gifted Education As a Field Adjust In Order To Recognize The Strengths And Assets Of Our Gifted Rural Studementioning
confidence: 90%
See 1 more Smart Citation
“…While they agreed that mandates were important, gifted education was equally so. Lewis and Boswell (2020) also found that consistent time blocks were an important aspect for gifted programs, from the perspective of teachers.…”
Section: How Does (Or Should) Gifted Education As a Field Adjust In Order To Recognize The Strengths And Assets Of Our Gifted Rural Studementioning
confidence: 90%
“…Further, the researchers acknowledged that their participants' "disparate ideals of success for their gifted students in the future alternated between materialistic ethics and wanting their students to live well in their rural community" (2020, p. 99) and that their "narratives acknowledged place-based ideals of success, such as local employment, family, and a general enjoyment of life, but these ideals were secondary to dominant conceptions of success, including education, acquisition, outmigration, and career status" (2020, p. 26) pointing to a potential push/pull conflict on the part of the students, as well as potential training for the teachers to recognize this conflict. Lewis and Boswell (2020) indicate that the need for training for both coordinators and teachers is substantial for their study participants; Davis et al (2020) concur, highlighting the need for teachers of color, as well as the need to train all teachers in cultural competency. "Culturally responsive education affirms the value of individual and cultural differences through the act of reducing or, better yet, eliminating prejudices, biases, microaggressions, and stereotypes based on sociocultural demographic variables" (Davis et al, 2020, p. 93).…”
Section: How Does (Or Should) Gifted Education As a Field Adjust In Order To Recognize The Strengths And Assets Of Our Gifted Rural Studementioning
confidence: 99%
“…Because the system is inexpensive, many countries have adopted the Raspberry Pi for educational purposes (Zhong, 2016). Lewis et al (2020) stated that rural areas have higher poverty rates than urban areas, contributing to low education and higher unemployment. Rural poverty also influenced access to health care and education.…”
Section: Discussionmentioning
confidence: 99%
“…In all levels of education, distance was a challenge to education. Students are also hindered by limited broadband access to many universities and colleges, while students do not have access to the internet at home (Lewis et al, 2020). Midland, Lubbock, El Paso, and Odessa in rural West Texas have 2.7 million underserved people with healthcare facilities.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation